Problematika Talak Online Via WhatsApp Perspektif Teori Hierarki Kebutuhan dan Maqashid al-Syari'ah - Ramadhani, Ika fitria; Ulya, Zakiyatul (Syariah: Jurnal Hukum Keluarga Islam, 2025)
The phenomenon of online ṭalāq conducted through digital media such as WhatsApp represents a new issue in divorce practices that generates legal, psychological, and social implications. This study aims to analyze the problems of online ṭalāq based on the hierarchy of human needs theory proposed by Abraham Maslow and the contemporary maqāṣid al-sharī‘ah perspective developed by Jasser Auda. The research employs a normative. The findings indicate that online ṭalāq from hierarchy of needs theory is associated with failures in fulfilling hierarchical human needs particularly the needs for security, affection, self-esteem, and self-actualization thereby encouraging emotional and hasty divorce decisions. From the maqāṣid al-sharī‘ah Jasser Auda perspective, the practice of online ṭalāq potentially conflicts with the objectives of Islamic law, including ḥifẓ al-dīn (protection of religion), ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-nasl (protection of progeny), ḥifẓ al-māl (protection of property), ḥifẓ al-karāmah al-insāniyyah (protection of human dignity), ḥifẓ al-usrah wa al-ḥuqūq al-usariyyah (protection of the family and family rights), and taḥqīq al-‘adālah al-ijtimā‘iyyah (realization of social justice), as it is often carried out without procedures that ensure legal certainty, justice, and family protection.